Perancangan Ulang Ruang Tunggu Dan Hall Stasiun Kereta Api Gambir, Jakarta Dengan Pendekatan Perilaku - Alifia Az Zahra, Shafira; Hambali Wilman Abdulhadi, Reza; Septony Siregar, Fernando (Telkom University, 2024)
This research aims to redesign the waiting area and hall of Gambir Station, Jakarta, using behavioral approach to enhance comfort and efficiency for users. As one of the busiest stations in Jakarta, Gambir Station has faced various issues such as inefficient layout and circulation, and suboptimal thermal comfort. This study analyzes different aspects of the station through primary data collection methods such as direct observation, interviews, and questionnaires, as well as secondary data from literature and government regulations. The findings indicate that the current design does not adequately accommodate the needs and behaviors of the users. Recommendations from this study include layout optimization, improvement of thermal comfort, and circulation adjustments more aligned with user behavior. With this redesign, Gambir Station is expected to become more efficient and comfortable for the thousands of passengers who use it daily, while ensuring the station remains a key transportation hub in Jakarta. This research also provides practical guidelines for other station management and contributes to the literature on transportation infrastructure design focused on user behavior aspects. Keywords: gambir station, redesign, behavioral approach, layout optimization, comfort